The significance of volcanic eruption strength and frequency for climate - Miles, G; Grainger, R; Highwood, E (Wiley, 2004)
A simple physical model of the atmospheric effects of large explosive volcanic eruptions is developed. Using only one input parameter - the initial amount of sulphur dioxide injected into the stratosphere - the global-average stratospheric optical-depth perturbation and surface temperature response are modelled. The simplicity of this model avoids issues of incomplete data (applicable to more comprehensive models), making it a powerful and useful tool for atmospheric diagnostics of this climate forcing mechanism. It may also provide a computationally inexpensive and accurate way of introducing volcanic activity into larger climate models. The modelled surface temperature response for an initial sulphur-dioxide injection, coupled with emission-history statistics, is used to demonstrate that the most climatically significant volcanic eruptions are those of sufficient explosivity to just reach into the stratosphere (and achieve longevity). This study also highlights the fact that this measure of significance is highly sensitive to the representation of the climatic response and the frequency data used, and that we are far from producing a definitive history of explosive volcanism for at least the past 1000 years. Given this high degree of uncertainty, these results suggest that eruptions that release around and above 0.1 Mt SO₂ into the stratosphere have the maximum climatic impact.